2017
DOI: 10.1371/journal.pone.0182846
|View full text |Cite
|
Sign up to set email alerts
|

Liver tissue fragments obtained from males are the most promising source of human hepatocytes for cell-based therapies – Flow cytometric analysis of albumin expression

Abstract: Cell-based therapies that could provide an alternative treatment for the end-stage liver disease require an adequate source of functional hepatocytes. There is little scientific evidence for the influence of patient’s age, sex, and chemotherapy on the cell isolation efficiency and metabolic activity of the harvested hepatocytes. The purpose of this study was to investigate whether hepatocytes derived from different sources display differential viability and biosynthetic capacity. Liver cells were isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
2
1
2
Order By: Relevance
“…Though gender did not have a significant effect on yield, a significant difference on viability was found between genders, with female donors having consistently higher viabilities than male donors, even when failed isolations were not considered. This is somewhat contrary to recent evaluation of hepatocytes isolated from resected livers, where it was found that hepatocytes from male donors were better suited by FACS analysis 16 . It is possible that the difference lies in the whole organ vs. resected livers as the tissue source for isolation; liver fragments are in general obtained during tumor resections and tend to be fresh and higher quality for isolation 1719 .…”
Section: Discussioncontrasting
confidence: 92%
“…Though gender did not have a significant effect on yield, a significant difference on viability was found between genders, with female donors having consistently higher viabilities than male donors, even when failed isolations were not considered. This is somewhat contrary to recent evaluation of hepatocytes isolated from resected livers, where it was found that hepatocytes from male donors were better suited by FACS analysis 16 . It is possible that the difference lies in the whole organ vs. resected livers as the tissue source for isolation; liver fragments are in general obtained during tumor resections and tend to be fresh and higher quality for isolation 1719 .…”
Section: Discussioncontrasting
confidence: 92%
“…CAR positivity was assessed using either recombinant ErbB2/Her2-Fc Chimera (1129-ER-050, R&D Systems) with anti-Human IgG-Fc-DyLight 650 (ab98622, Abcam) or with biotinylated recombinant protein L (29997, Thermo Fisher Scientific) and anti-biotin-PE (12-9895-82, eBioscience). Primary mouse hepatocytes were gated using the gating schema described previously (47), and fluorescence from IRFP720 protein was detected in the AF100 spectrum (Supplemental Figure 6).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Also, the decreased amount of total ALB levels Fig. 4 induced by CCl 4 is a further indication of liver damage, decrease in the number of hepatocytes which in turn may result in a decrease in hepatic capacity to synthesize albumin 24 . Therefore decreased levels of albumin as recorded in CCl 4 -induced rats revealed liver injury and may be attributed to the damage produced and localized in the endoplasmic reticulum leading to decrease in protein synthesis 25 .…”
Section: Discussionmentioning
confidence: 99%